Effect of dietary betaine (CH3)3N+CH2CO−2) fortifications on growth performance, carcass traits, and blood biochemistry of broilers under heat stress condition - Mohamed I. Elmahdy; Mohamed S. El-Kholy; Samar S. Bassiony; Shaker M. Abolmaaty; Mahmoud M. Azzam; Seham El-Kassas; Mahmoud Alagawany; Antonia Lestingi (Results in Chemistry)
Betaine (Trimethylglycine) has been used as a supplement for both animals and plants. The current study examined the potential replacement of antibiotics in broilers diet with safe alternatives. Accordingly, different levels of betaine (0, 1.5, 2, and 2.5 g/kg diet) were supplemented to the basal diet compared with the antibiotic growth promoter (oxytetracycline) at 0.50 g/kg diet and randomly distributed in a completely randomized design with 5 groups and 5 replicates per group (n = 10 birds/replicate). The experiment lasted for 35 days with ad libitum access to feed and water and Ross-308 broilers raised under heat stress condition. Different levels of betaine supplementation, particularly the 2.5 g betaine/ kg of diet improved growth performance of broilers exposed to prolonged high temperatures (P < 0.05). Moreover, presence of betaine in broilers diet alleviated the negative impacts of high temperatures in summer by increasing superoxide dismutase (SOD), and catalase (CAT) activities with a significant reduction in lipid peroxidation. Betaine caused increases in immunoglobulins levels especially IgM which was associated with marked increases in bursa relative weights in broilers supplemented with 2.5 g betaine/kg diet. The different levels of betaine resulted in a healthier lipid profile by reducing the serum levels of triglyceride (TG), total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL) and very low density lipoprotein (VLDL). In conclusion, betaine dietary fortification, particularly at 2.5 g/kg diet could be an effective alternative to antibiotics in broilers' diets.